SARS-CoV-2 lineage B.6 was the major contributor to early pandemic transmission in Malaysia. - Yoong Min Chong; I-Ching Sam; Jennifer Chong; Maria Kahar Bador; Sasheela Ponnampalavanar; Sharifah Faridah Syed Omar; Adeeba Kamarulzaman; Vijayan Munusamy; Chee Kuan Wong; Fadhil Hadi Jamaluddin; Yoke Fun Chan (Public Library of Science (PLoS), 2020)
Malaysia had 10,219 confirmed cases of COVID-19 as of September 20, 2020. About 33% were associated with a Tablighi Jamaat religious mass gathering held in Kuala Lumpur between February 27 and March 3, 2020, which drove community transmission during Malaysia's second wave. We analysed genome sequences of SARS-CoV-2 from Malaysia to better understand the molecular epidemiology and spread. We obtained 58 SARS-CoV-2 whole genome sequences from patients in Kuala Lumpur and performed phylogenetic analyses on these and a further 57 Malaysian sequences available in the GISAID database. Nine different SARS-CoV-2 lineages (A, B, B.1, B.1.1, B.1.1.1, B.1.36, B.2, B.3 and B.6) were detected in Malaysia. The B.6 lineage was first reported a week after the Tablighi mass gathering and became predominant (65.2%) despite being relatively rare (1.4%) globally. Direct epidemiological links between lineage B.6 viruses and the mass gathering were identified. Increases in reported total cases, Tablighi-associated cases, and community-acquired B.6 lineage strains were temporally linked. Non-B.6 lineages were mainly travel-associated and showed limited onward transmission. There were also temporally correlated increases in B.6 sequences in other Southeast Asian countries, India and Australia, linked to participants returning from this event. Over 95% of global B.6 sequences originated from Asia Pacific. We also report a nsp3-C6310A substitution found in 47.3% of global B.6 sequences which was associated with reduced sensitivity using a commercial diagnostic real-time PCR assay. Lineage B.6 became the predominant cause of community transmission in Malaysia after likely introduction during a religious mass gathering. This event also contributed to spikes of lineage B.6 in other countries in the Asia-Pacific. Mass gatherings can be significant causes of local and global spread of COVID-19. Shared genomic surveillance can be used to identify SARS-CoV-2 transmission chains to aid prevention and control, and to monitor diagnostic molecular assays. Clinical Trial Registration: COVID-19 paper.